The Influence of Workload, Marital Status, and Interpersonal Conflict on Work Stress Through Work Fatigue among Workers at PT PLN Indonesia Power Service Business Unit (UBP) Tello Makassar - Umayyah Marsya; Masyitha Muis; M. Furqaan Naiem; Syamsiar S. Russeng; A. Arsunan Arsin; Anwar Mallongi; Achmad Yoga Issaniyah (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Work stress is a growing issue in various industries, including at PT PLN Indonesia Power UBP Tello Makassar. It affects workers’ mental and physical health, productivity, and organizational performance. Key triggers include excessive workload, marital status, and interpersonal conflict. Objective: This study aimed to examine the influence of these factors on job burnout and stress using a quantitative, cross-sectional approach. Methods: Data from 215 workers were collected via questionnaires, also cocorometer to measure objective stress, the data then analyzed statistically. Results: The study results showed a direct effect of workload on stress (p = 0.000) but no significant effect with the cocorometer (p = 0.566). Workload also indirectly affected stress through fatigue (p = 0.006), though not significantly with the cocorometer (p = 0.099). Marital status had a direct impact on stress (p = 0.000), but not with the cocorometer (p = 0.710). Interpersonal conflict showed no direct influence on stress in the questionnaire (p = 0.899), but was significant with the cocorometer (p = 0.000). Conclusions: In conclusion, high workload, marital status, and interpersonal conflict contribute to job stress, emphasizing the need for interventions to reduce workload and improve workplace conditions.